The shear-driven transformation mechanism from glassy carbon to hexagonal diamond. (February 2019) - Wong, S.; Shiell, T.B.; Cook, B.A.; Bradby, J.E.; McKenzie, D.R.; McCulloch, D.G.
Abstract: Hexagonal diamond, a potentially superhard material, forms from a glassy carbon precursor at pressures of ∼100 GPa at the relatively low temperature of 400 °C. The formation mechanism of the hexagonal diamond phase was investigated by performing microstructural analysis on cross-sections of the recovered samples. Three distinct structures have been observed, a graphitic region near the centre of the sample with low density, a hexagonal diamond region at the edge of the sample with high density, and a mixed region containing significant proportions of both the graphitic structure and hexagonal diamond. The hexagonal diamond was more likely to occur at greater radial distance from the centre of the sample with some evidence for greater amounts also near the diamond anvil faces. The observed distribution of the hexagonal phase correlates well to regions of greatest shear strain expected from modelling studies of strain fields in diamond anvil cells. The findings support the proposition that shear strain plays an important role in the formation of hexagonal diamond, and that it may be a driving force for the natural occurrence of hexagonal diamond in the shear zone of meteorite impact craters. Graphical abstract: Image